Problematising international social work placements as a site of intercultural learning - Parker, Jonathan; Ashencaen, Crabtree; Azlinda, Azman; Carlo, Dolly Paul; Cutler, Claire (European Journal of Social Work, 2014)
This paper theorises some of the learning outcomes of a three-year project concerning student learning in international social work placements in Malaysia. The problematic issue of promoting cultural and intercultural competence through such placements is examined, where overlapping hegemonies are discussed in terms of isomorphism of social work models, that of the nation state, together with those relating to professional values and knowledge, and the tyrannies of received ideas. A critical discussion of cultural competence as the rationale for international placements is discussed in terms of the development of the graduating social worker as a self-reflexive practitioner. The development of sustainable international partnerships able to support student placement and the issue of non-symmetrical reciprocation, typical of wide socio-economic differentials across global regions, is additionally discussed.